Correction: Impacts of a near-future supersonic aircraft fleet on atmospheric composition and climate. Issue 3 (26th April 2022) - Eastham, Sebastian D.; Fritz, Thibaud; Sanz-Morère, Inés; Prashanth, Prakash; Allroggen, Florian; Prinn, Ronald G.; Speth, Raymond L.; Barrett, Steven R. H.
Abstract : Correction for 'Impacts of a near-future supersonic aircraft fleet on atmospheric composition and climate' by Sebastian D. Eastham et al., Environ. Sci.: Atmos., 2022, ; https://doi.org/10.1039/D1EA00081K .